2021
DOI: 10.1002/adom.202102074
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Exciton Enhanced Radioluminescence of Ga3+/Tb3+ Metallacrown Scintillators for X‐Ray Detection

Abstract: The increasing demand for radiation detection in many applications has led to demanding requirements for scintillators. Realizing low‐dose, pollution‐free, and reliable X‐ray detection has become a key technical challenge. Here, a triplet‐enhanced lanthanide radioluminescence (RL) material Ga3+/Tb3+ metallacrowns (Tb‐1) is reported. This Tb‐1 crystal emits bright green luminescence under ultraviolet light or X‐ray excitation, and the emission intensity is 286 and 242 times that of Tb3+ in inorganic salt, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…25 However, their potential as scintillators has been largely underexplored, with very few cerium and lanthanidebased organic metal complexes reported to exhibit low light yields. 26,27 Also, the presence of heavy atoms in these organic metal complexes often leads to long-lived phosphorescent emissions, which is undesirable for dynamic X-ray imaging, high-energy particle physics research, and many other applications. Therefore, further the exploration of organic metal complexes is necessary to develop efficient, rapid, and solutionprocessable scintillators.…”
Section: View Article Onlinementioning
confidence: 99%
“…25 However, their potential as scintillators has been largely underexplored, with very few cerium and lanthanidebased organic metal complexes reported to exhibit low light yields. 26,27 Also, the presence of heavy atoms in these organic metal complexes often leads to long-lived phosphorescent emissions, which is undesirable for dynamic X-ray imaging, high-energy particle physics research, and many other applications. Therefore, further the exploration of organic metal complexes is necessary to develop efficient, rapid, and solutionprocessable scintillators.…”
Section: View Article Onlinementioning
confidence: 99%
“…The high coupling and spectral overlap between the organic ligands and lanthanide ions facilitate efficient intersystem crossing, converting some of these excitons from singlet states to triplet states in the organic molecules. The triplet-state energy is then transferred from the organic ligands to the lanthanide ions through nonradiative resonance energy transfer, resulting in strong XEL emission. , …”
mentioning
confidence: 99%
“…The triplet-state energy is then transferred from the organic ligands to the lanthanide ions through nonradiative resonance energy transfer, resulting in strong XEL emission. 20,21 To assess the feasibility of Eu-pba and Tb-pba for practical applications, we investigated the hydrolytic, radiation, and thermal stabilities of both complexes. PXRD analyses revealed that the structures of Eu-pba and Tb-pba remained unchanged when exposed to different relative humidity (RH) conditions ranging from 45% to 100% for 24 h (Figure 2d).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 With the growing demand for radiation detection, the requirements for scintillators are increasing. 3 Designing ultrabright and ultrafast scintillators has been a primary goal in this field since high light yield can realize detection at low irradiation dosage; ultrafast decay time can realize good time resolution and response rate of detectors. 4 Scintillators are approaching their theoretical limit in light yield, but there is still much potential for improvement in the decay time/response time.…”
mentioning
confidence: 99%